Services Trade Restrictiveness, Mark-Ups and Competition - Rouzet, Dorothée (OECD Trade Policy Papers, 2016)
This report explores the relationship between services trade policies and mark-ups at the firm level, taken as a measure of competitive pressure. Restrictive regulations are found to enable firms to charge higher mark-ups in a majority of services sectors, suggesting ample scope for pro-competitive gains from trade liberalisation. Barriers to establishment consistently enable incumbent firms shielded from competition to raise their prices, while a lack of regulatory transparency and complex administrative procedures tend to add to all firms' operating expenses. A "tax equivalent" of trade-restrictive regulations is then inferred from the abnormal price-cost margin of domestic firms in each service sector. These estimates indicate the magnitude of the welfare costs of regulatory trade restrictions across sectors and countries. The sectors with the highest average tax equivalents of STRI indices are broadcasting, construction, storage, and air and maritime transport, while those with the lowest averages are road transport, architecture and cargo-handling. There is however considerable variation between countries in all sectors